The Effectiveness of Using Automatic Embroidery in the Costumes of the Tourist Guide of the City of Neom and its Impact on Raising the Culture of The Region (The International Journal for Scientific Research, 2023)
The effectiveness of using automatic embroidery methods in the clothes of the tourist guide of the city of Neom and its impact on raising culture. The research problem is summarized in the effectiveness of the use of automatic embroidery methods in the clothes of the tourist guide of the city of  Neom and its impact on raising culture, and the importance of the research lies in the development of the general form of the tour guide uniform by integrating the skills of automatic embroidery and achieving new creative entrances to employ automatic embroidery  in the form of the logo of the city of Neom on the vests of tourist guides and is represented in cutting his clothes, and the researcher followed the study of the applied descriptive approach where the descriptive approach was In the use of automatic embroidery stitches padding stitch and the applied approach in the implementation of stitches  on the vest of the tour guide in the city of  Neom was also distributed questionnaire to extract results and information, and the research hypotheses lie in the relationship between the development of the general form of the tourist guide uniform and the integration of automatic embroidery skills and the achievement of new creative entrances and there is a relationship between the employment of automatic embroidery in the form of the logo of the city of Neom on the vests of tourist guides in the city of Neom and is represented in the pieces  of clothing As the researcher summarizes the results of the research, there is a statistically significant relationship between the development of the general shape of the tour guide uniform and the integration of automatic embroidery skills and the achievement of new creative entrances and appears in the ninth phrase by 70% strongly agree "innovation of automatic embroidery techniques in the clarity of the role of the tour guide", and  there is a statistical relationship between the employment of automatic embroidery in the form of the logo of the city of Neom on the vests of tourist guides in the city of Neom and is represented in the pieces of clothing and appear in the twentieth phrase by 73% strongly agree "with a significance level of 0.000.The association of the art of machine embroidery with the NEOM logo led to the renaissance of manual skills", and the  researcher recommends paying attention to machine embroidery, which leads to the renaissance of manual skills for the logo of Neom city and the establishment of training courses to educate the tourist guide in the field of tourism development in NEOM.
Keywords: Robotic Embroidery; Tour Guide